ECONOMIC CRISIS IN THE BALTIC STATES: FOCUSING ON LATVIA - Koyama, Yoji (Economic Annals, 2010)
This paper examines the causes of the economic crisis in new EU member states in Central and Eastern Europe, focusing on the Baltic States, especially Latvia. Thanks to the Single Market of the EU, workers in this country became able to migrate to advanced EU countries, especially the UK, decreasing the unemployment rate and at the same time causing a sharp increase in wages due to a tightened labour market. Banks from Nordic countries came to operate in Latvia and competed for market shares, stirring a consumption boom. In a situation in which people can easily get loans denominated in a foreign currency the monetary policies of the central bank are weakened. The Latvian economy already showed signs of overheating in 2005. However in the spring of 2007 the government turned to restrictive policies, causing a depression at the end of 2007. The Lehman shock dealt the Latvian economy its final blow. Latvia set up the introduction of the Euro in 2013 as an exit strategy. Latvia is in a dilemma: if the country does not devalue its national currency and tries to satisfy the Maastricht criteria soon, it will be obliged to adopt pro-cyclical policies, causing economic stagnation.